Discovering Indonesia: Video Reactions of Jiwa Jagad Jawi Storynomic Tourism - Dian Arymami (Ikatan Sarjana Komunikasi Indonesia, 2023)
The storynomic tourism approach uses the power of storytelling in the effort to enhance quality tourism and promote destinations. In enhancing this approach a promotional video of Java, called Jiwa Jagad Jawi was launched in 2022 in a theme of rediscovering the mind, body, and soul of Java whilst promoting several destinations in Java. The video ignited multiple reaction videos from Youtubers around the world, a vernacular form of visual production where the Youtuber reacts to a certain media content. Reaction videos towards Jiwa Jagad Jawi holds an interpretation of Java from the creator as well as a production of representation of Java as a destination in the text. Thus, putting video reactions of Jiwa Jagad Jawi as a digital work that extends its designated promotional means with a situated cultural experience of the creator; reframing narration of the destination to their viewers and followers. The present study focuses on “reaction videos” on YouTube towards Jiwa Jagad Jawi in exploring representation and interpretation of the culture and destination. The exploration of interpretation and production in reaction videos of tourism storynomics may offer an understanding to the dynamics of tourism promotional videos in this digitalscape. For the analysis of this exploration, an audience reception framework situated in cultural studies is used to study the reaction videos and comments. The study has found reaction videos as a significant promotional tool that drives further narrations of Indonesia and the reproduction of perceived Java as a destination of peace, serenity, mystical and culturally rich destination.